Integrated study of experiment and first‐principles computation for the characterization of a corium type ZrO8 complex in a Zr‐doped fluorite UO2. (21st March 2019) - Lee, Jeongmook; Kwon, Choah; Kim, Jandee; Youn, Young‐Sang; Kim, Jong‐Yun; Han, Byungchan; Lim, Sang Ho
Summary: We, for the first time, observe ZrO8 complex in Zr‐doped UO2, which is a corium structure, using experimental characterization integrated with first‐principle computational validation. Atomic level structure of U1− y Zr y O2 pellets ( y  = 0.01, 0.03, 0.05, and 0.1) is identified using Raman spectroscopy measurement and X‐ray diffraction pattern analysis. The lattice constants shrink with increasing Zr doping levels, which consistently represents in the positive shift of T2g Raman vibration peak around 445 cm −1 . More interestingly, conventionally unknown new Raman peak appears around 598 cm −1, which has not been observed in neither a pure ZrO2 nor UO2 doped with tetravalent elements other than Zr. We unveil that the new peak originates from ZrO8 ‐type complex formed on the fluorite UO2 . Our study provides precise understanding on the formation mechanisms and material properties of the corium in the hypervalent oxide. Abstract : Integrated experimental‐computational study on ZrO2 ‐UO2 solid solution revealed strong evidence for Zr incorporation into UO2 fluorite structure as the Zr‐O8 coordinate. XRD analysis and Raman spectroscopic observation were consistently supported by first‐principle calculations, and it was clearly shown that ZrO8 ‐type complex forms in the fluorite UO2 matrix via successive accommodation of doped Zr. Variation of the calculated lattice parameters with Zr doping levels and analysis of unique vibrational peak position of O in U1− y Zr y O2 validated the experimental observation.